A few-emitter solid-state multi-exciton laser - S. Lichtmannecker (Nature Portfolio, 2017)
Abstract We report on non-conventional lasing in a photonic-crystal nanocavity that operates with only four solid-state quantum-dot emitters. In a comparison between microscopic theory and experiment, we demonstrate that irrespective of emitter detuning, lasing with $${g}^{(2)}=1$$ g (2) = 1 is facilitated by means of emission from dense-lying multi-exciton states. In the spontaneous-emission regime we find signatures for radiative coupling between the quantum dots. The realization of different multi-exciton states at different excitation powers and the presence of electronic inter-emitter correlations are reflected in a pump-rate dependence of the β-factor.